Efektivitas Layanan Bimbingan Konseling Kelompok Terhadap Konsep Diri Remaja Korban Bully di SMK Negeri 1 Lotu - Dirga Krisna Zega; Hosiana R. Damanik; Famahato Lase; Mondang Munthe (Journal on Education, 2024)
Based on the results of interviews with several teachers, it was found that grade X students of SMK Negeri 1 Lotu still have many teenage students who have poor self-concept due to the bullying actions they receive. As for several factors that cause poor self-concept of adolescent students From these findings, researchers made a study with the aim of knowing the picture of changes in the self-concept of bully victim students in class X of SMK Negeri 1 Lotu through group counseling guidance services.This study uses quantitative methods with a descriptive approach, with the formulation of the research problem describing the results of group counseling guidance to students who are victims of bullying seen from the level of student self-concept. In this case, researchers distributed questionnaires to find out the level of students' self-concept and then counseling guidance was carried out on students who had a high level of bullying. The results of this counseling guidance will be described using percentages. The number of samples distributed by the self-concept questionnaire was 100 people. The results stated that the self-concept of bully victims at SMK Negeri 1 Lotu was classified as "Medium" with a percentage of 67.79%. But there are still 30 students who have a "High" or "Very High" self-concept . The cause of students who have a self-concept of bullying victims who are "High" or "Very High" is first because they are less able to improve themselves, not optimistic about themselves, causing a lack of student confidence and unable to overcome problems on their own. The results of the implementation of counseling guidance services for students victims of adolescent bullying in general are "Very Effective" with an average percentage of 86.4%.